2010
DOI: 10.1111/j.1365-3059.2010.02317.x
|View full text |Cite
|
Sign up to set email alerts
|

Mendelian inheritance of rust resistance to Melampsora larici‐epitea in crosses between Salix sachalinensis and S. viminalis

Abstract: Two F 1 , two F 2 and two backcross (BC) full-sib families of Salix sachalinensis · S. viminalis were tested for resistance to two pathotypes of Melampsora larici-epitea in leaf-disc inoculation experiments. Two single-pustule isolates, VM and ST, belonging to pathotypes LET1 and LET5, respectively, were used in the tests. Disease was scored based on the number of uredinia, uredinial diameter and inoculum densities. Both F 1 families were completely resistant to both VM and ST. Resistance to VM segregated at a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…A remarkable high genic diversity in resistance genes has been described in the related species P. trichocarpa where around 400 NBS class resistance genes have been found (Kohler et al 2008). In a recent study by Pei et al (2010), a Mendelian inheritance of rust resistance was indicated for major genes in hybrid crossings S. sachalinensis×S. viminalis.…”
Section: Discussionmentioning
confidence: 96%
“…A remarkable high genic diversity in resistance genes has been described in the related species P. trichocarpa where around 400 NBS class resistance genes have been found (Kohler et al 2008). In a recent study by Pei et al (2010), a Mendelian inheritance of rust resistance was indicated for major genes in hybrid crossings S. sachalinensis×S. viminalis.…”
Section: Discussionmentioning
confidence: 96%
“…Rust pathotypes and genotype resistance in the UK has been studied, but there is poor understanding of the Melampsora pathotypes affecting willow species in North America [39,[44][45][46][47]. Previous studies have shown that Melampsora resistance is highly heritable and has already been exploited in breeding for rust resistance through hybridization with Salix schwerinii [44,46,[48][49][50].…”
Section: Rust Incidence and Beetle Damage And Specificitymentioning
confidence: 99%
“…Willow breeding has traditionally exploited the high genetic diversity and heterozygosity inherent among natural populations [7]. The main breeding strategies for willow in the USA, UK, and Sweden have been to improve biomass yield by capturing heterosis through the production of interspecific hybrids [8,9,4]; however, breeding for pest and disease resistance has also been of high priority due to detrimental effects on growth and production [10][11][12]. It is well documented that heterosis is a common phenomenon observed among hybrid progeny in many plant species and also among polyploid individuals [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%